Boundaries of American Identity: Relations Between Ethnic Group Prototypicality and Policy Attitudes. Issue 4 (1st April 2014) - Huynh, Que‐Lam; Devos, Thierry; Altman, Hannah R.
<x xml:space="preserve">Abstract</x> We sought to document that the extent to which different ethnic groups are perceived as embodying the American identity is more strongly linked to antiminority policy attitudes and acculturation ideologies among majority‐group members (European Americans) than among minority‐group members (Asian Americans or Latino/as). Participants rated 13 attributes of the American identity as they pertain to different ethnic groups and reported their endorsement of policy attitudes and acculturation ideologies. We found a relative consensus across ethnic groups regarding defining components of the American identity. However, European Americans were perceived as more prototypical of this American identity than ethnic minorities, especially by European American raters. Moreover, for European Americans but not for ethnic minorities, relative ingroup prototypicality was related to antiminority policy attitudes and acculturation ideologies. These findings suggest that for European Americans, perceptions of ethnic group prototypicality fulfill an instrumental function linked to preserving their group interests and limiting the rights afforded to ethnic minorities.